Advanced Technology Investment, Transfer, Export and Import: Determinants or Predictors of Economic Growth and Inflation Fluctuations? - Iryna Pozovna; Dariusz Krawczyk; Vadym Babenko (Financial Markets, Institutions and Risks)
Investments, scientific patents, export and import of high-tech goods and services stimulate the country’s technological development, contribute to economic growth, job creation, the formation of a qualified workforce, and the maintenance of social living standards of the population. At the same time, the ecosystem supporting technological innovation is largely dependent on macroeconomic stability in the country, inflationary fluctuations, etc. Based on this, the article examines systemic interrelationships between the factors of technological development (export and import of computer, information, telecommunications and other high-tech goods and services, investments in advanced research and technologies, volumes of transfer of rights to new technological developments, as well as general the level of coverage of the population by information technologies and innovativeness of the country) and macroeconomic development (gross domestic and national product, inflation rate). The research was carried out using the method of Principal component analysis, canonical analysis, panel regression modeling on the data of 11 countries with developed economies for 2011 and 2021 (World Bank and WIPO statistical databases). From 14 indicators of technological development, the 8 most relevant ones were selected using the method of Principal component analysis; by means of canonical analysis, it was found that 32.503% (in 2011) and 37.557% (in 2021) of their variation is due to changes in the studied macroeconomic indicators. On the other hand, the change in macroeconomic indicators by 46.497% (in 2011) and 38.739% (in 2021) is caused by the variation of indicators of investment, transfer, export and import of advanced technologies. Thus, macroeconomic dynamics depend much more on technological development, and not vice versa. Based on the conducted panel regression modeling, a statistically significant dependence of the inflation index on the share of the population that is Internet users and the country's place in the Global Innovation Index was revealed. GDP per capita was found to be dependent on the share of exports of high-tech goods and services, the share of exports of goods in the field of information and communication technologies, the share of the population that are Internet users, the country's place in the Global Innovation Index. State investments in research and technological development turned out to be dependent on the inflation index, the share of imports of computer, information and other services, the share of exports of goods in the field of information and communication technologies, the share of the population that are Internet users, and the country’s place in the Global Innovation Index.